Subtitling Analysis Of Utterances FoundIn Frozen Movie - Nurlatifasari, Rida, Dr. Dwi Haryanti, M.Hum (2016)
This research focuses on Speech Act and subtitling quality of Frozen movie. This research is descriptive qualitative research. The purposes of this research are: (1) To identify of speech act sentences and their subtitling found in Frozen movie; (2)To describe the subtitling quality of English into Indonesian translation of Frozen movie. The data are analyzed based on the theories of Speech Act and subtitling quality. The data of this research are utterances containing speech act (declarative, representative, expressive, commissive, and directive utterance) from the data source. The data source is the subtitling of Frozen movie by Jenifer Lee. The results of this research show that there are 1342 data. The researcher finds five English Speech Act classification are: (1) 223 data to Declarative, (2) 544 data to Representative, (3) 188 data to Expressive, (4) 34 data to Commissive, (5) 353 data to Directive. The researcher finds five Indonesian Speech Act classification are: (1) 223 data toDeclarative, (2) 544 data to Representative, (3) 179 data to Expressive, (4) 35 data to Commissive, (5) 353 data to Directive.There are three aspects for good quality that subtitling should fulfill: accuracy, acceptability, and readability: (1) 1245 data or 92,63 % accurate, (2) 55 data or 4,163 % less accurate, (3) 42 data or 3,19 % inaccurate, (4) 1326 data or 98,81 % acceptable, (5) 6 data or 0,52 % less acceptable, (6) 9 data or 0,67 % unacceptable, (7) 1326 data or 98,81 % high readability level, (8) 9 data or 0,67% moderate readability level, and (9) 7 data or 0,52 % low readability level.